Type developing an Islamic education curriculum on outcomes-based education as a defensive strategy facing the challenges of industry revolution 4.0 - Suyadi Suyadi (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
The Revolution of Industry 4.0 threatens the existence of the science of Islamic education if the curriculum is not outcomes based. The development of Islamic higher education curriculum allows the creation of new academic subjects which integrates learning, research and service to produce innovative and tested work. The aim of this research is to put forward a curriculum development model or prototype as a strategy to maintain the science of Islamic education learning programs in the era of Industry Revolution 4.0. The research approach is qualitative of the phenomenological type. The setting of the research is the learning program for the Masters in Islamic Education (Magister Pendidikan Agama Islam – MPAI), Faculty of Islam, Ahmad Dahlan University. The choice of this research setting is because the curriculum of this learning program has created new academic subjects which have an outcome-based integrated learning, research and service, as a result on reaching the three year point it has gained full accreditation from the Higher Education National Accreditation Board (Badan Akreditasi Nasional–Perguruan Tinggi – BAN-PT). Respondents in the research are the MPAI academic community which comprise six lecturers including the Chair of the Study Program and Secretariat of the Study Program together with eighty students studying at the masters level. The research results show that the MPAI learning program has created two new academic subjects that is, Islamic Education Studies and Intellectual Property Rights (Hak Kekayaan Intelektual – HKI) together with Neuroscience and Islamic Education Theory. Both new subjects have mobilized research which has produced innovative works obtaining more than sixty intellectual property rights and occupying the first rank in publications in national and international journals in the the Sinta Index 2020 data base. This shows that this learning program is able to maintain a scientific existence in the era of the industry revolution through outcome-based curriculum development.